2020
DOI: 10.1097/phm.0000000000001443
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation After Critical Illness in People With COVID-19 Infection

Abstract: The current COVID-19 pandemic will place enormous pressure on healthcare systems around the world. Large numbers of people are predicted to become critically ill with acute respiratory distress syndrome and will require management in intensive care units. High levels of physical, cognitive, and psychosocial impairments can be anticipated. Rehabilitation providers will serve as an important link in the continuum of care, helping move patients on from acute sites to eventual discharge to the community. Likely im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
277
0
52

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 279 publications
(344 citation statements)
references
References 60 publications
2
277
0
52
Order By: Relevance
“…Although it has been suggested that ideally patients admitted to IRFs should either be asymptomatic or test COVID negative, we took a different approach given the overwhelming volume of COVID-19 positive patients in our area. 9 Given our limited knowledge about this disease and its course, these decisions were made on a case-by-case basis. We did find that patients with downward trending inflammatory markers and either normal or downward trending ferritin levels tended to be more appropriate for admission to our freestanding acute rehabilitation hospital.…”
Section: Administrative Challengesmentioning
confidence: 99%
“…Although it has been suggested that ideally patients admitted to IRFs should either be asymptomatic or test COVID negative, we took a different approach given the overwhelming volume of COVID-19 positive patients in our area. 9 Given our limited knowledge about this disease and its course, these decisions were made on a case-by-case basis. We did find that patients with downward trending inflammatory markers and either normal or downward trending ferritin levels tended to be more appropriate for admission to our freestanding acute rehabilitation hospital.…”
Section: Administrative Challengesmentioning
confidence: 99%
“…Mental dysfunction is also very prevalent in HCWs without coronavirus diagnoses, with to studies (41,57) nding > 25% prevalence for distress and psychiatric morbidity. Many sources re ected upon the additional psychological burden experienced by HCWs, due to ethical tensions around not being able to meet previously expected levels of service, balancing exposure with social contact, and surge management challenges (58)(59)(60)(61)(62)(63)(64)(65). These burdens are described as growing over time (58,59), with HCWs who are single, female, nurses and doctors, frontline workers and close to outbreaks noted to be at particular risk (41,57).…”
Section: Resultsmentioning
confidence: 99%
“…The only current recommendation for patients is the use of early mobilisation wherever possible (62,69).…”
Section: Mobilitymentioning
confidence: 99%
See 2 more Smart Citations